Step
*
1
1
1
1
1
1
1
1
1
of Lemma
mod2-add1
.....assertion..... 
1. n : ℤ
2. a : ℤ
3. b : ℤ
4. c : ℤ
5. d : ℤ
6. (((b + b) + d) + 1) = ((a + a) + c) ∈ ℤ
7. n = ((b * 2) + d) ∈ ℤ
8. ∀x:ℤ. ((2 * x) = (x + x) ∈ ℤ)
9. ∀x:ℤ. ((x * 2) = (x + x) ∈ ℤ)
⊢ c = ((((b + b) + d) + 1) - a + a) ∈ ℤ
BY
{ ((MoveToConcl 6 THEN GenConclTerms Auto [ ⌜((b + b) + d) + 1⌝;⌜a + a⌝]⋅) THEN All Thin) }
1
1. c : ℤ
2. v : ℤ
3. v1 : ℤ
⊢ (v = (v1 + c) ∈ ℤ) 
⇒ (c = (v - v1) ∈ ℤ)
Latex:
Latex:
.....assertion..... 
1.  n  :  \mBbbZ{}
2.  a  :  \mBbbZ{}
3.  b  :  \mBbbZ{}
4.  c  :  \mBbbZ{}
5.  d  :  \mBbbZ{}
6.  (((b  +  b)  +  d)  +  1)  =  ((a  +  a)  +  c)
7.  n  =  ((b  *  2)  +  d)
8.  \mforall{}x:\mBbbZ{}.  ((2  *  x)  =  (x  +  x))
9.  \mforall{}x:\mBbbZ{}.  ((x  *  2)  =  (x  +  x))
\mvdash{}  c  =  ((((b  +  b)  +  d)  +  1)  -  a  +  a)
By
Latex:
((MoveToConcl  6  THEN  GenConclTerms  Auto  [  \mkleeneopen{}((b  +  b)  +  d)  +  1\mkleeneclose{};\mkleeneopen{}a  +  a\mkleeneclose{}]\mcdot{})  THEN  All  Thin)
Home
Index